2021
DOI: 10.24269/ekuilibrium.v16i1.3364
|View full text |Cite
|
Sign up to set email alerts
|

The Impact on Economic and Environmental Development of COVID-19 Pandemic: a Case Study in Indonesia

Abstract: The goal of this analysis is to examine in greater detail the effect of the COVID-19 pandemic on economic development and the quality of the atmosphere in Indonesia. This report uses secondary data as the primary source, obtained using a secondary data collection method from many different organizations. Different government policies and measures to discourage the escalation of the transmission of the Coronavirus, one of which is large-scale social restrictions (PSBB). However, before Indonesia suffered a rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The epidemic has had a devastating impact on human health and life. It has caused unprecedented disruptions in production, consumption, investment, supply chains, tourism, and trade, and it has had a profound effect on the economy of China and the world (Dewi and Melati, 2021;Ferreira et al, 2021;Karn, 2021). In terms of the impact of COVID-19 on labor demand and supply, market wage level and employment rate, some scholars found that COVID-19 had a dual impact on labor demand and supply.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The epidemic has had a devastating impact on human health and life. It has caused unprecedented disruptions in production, consumption, investment, supply chains, tourism, and trade, and it has had a profound effect on the economy of China and the world (Dewi and Melati, 2021;Ferreira et al, 2021;Karn, 2021). In terms of the impact of COVID-19 on labor demand and supply, market wage level and employment rate, some scholars found that COVID-19 had a dual impact on labor demand and supply.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many MSMEs owners have gone bankrupt in this pandemic era. The implementation of largescale social restriction policies (Dewi & Melati, 2021) forced most of them to close their business stalls. In addition, changes in consumption patterns and people's lifestyles also have an impact on the demand for MSMEs products.…”
Section: Literature Review Micro Small and Medium Enterprises (Msmes)mentioning
confidence: 99%
“…Indonesia is a developing country that strives to carry out sustainable development to become a developed country. The pandemic that hit not only had an impact on the health sector but also threatened to reduce social and economic activities in the world (Dewi & Melati, 2021). The total population of poor in Indonesia was 27,54 million inhabitants in March 2021, with a percentage of 10,14 percent, an increase from the percentage of poverty in March 2020, which was 9.78 percent.…”
Section: Introductionmentioning
confidence: 99%